An Introduction to Cognitive Constructivism in Education - Kumar, Rajesh; Gupta, V.K. (JOURNAL OF INDIAN EDUCATION, 2009)
Many theories of learning have been proposed in the last century until recently, behavioural psychology has influenced education to such a starting degree that it had a virtual stronghold on how textbooks were defined and how teachers planned and implemented lessons. Constructivism reflects this philosophy; Cognitive Constructivism is based on the work of Swiss developmental psychologist Jean Piaget. Piaget’s theory of cognitive development proposes that humans can not be ‘given’ information which they immediately understand and use. Instead, humans must ‘construct’ their own knowledge. They build their knowledge through experience. Experiences enable them to create schemes – mental models in their heads. These schemes are changed, enlarged and made more sophisticated through two complimentary processes: assimilation and accommodation.